Darwin tra le macchine? L’intelligenza della tecnoscienza - Amato, Salvatore (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2023)
Balzac, Hugo, Butler, attracted by the scientific developments that accompanied the emergence of industrial society, hypothesised the radicality of a new era in which it would be possible to arrive at knowledge of the essence of all things. To find the soul of the world or a world without a soul? Today, it is mechanistic reductionism, fuelled by developments in artificial intelligence and the suggestions of Core theory, that re-proposes the dispute between matter and spirit, presenting us with the image of a world in which everything is random and everything is manipulable. It is precisely its extreme achievement, the reproduction of thought, that seems to transcend matter, because we cannot exclude that new technologies are consolidating around a particular form of intelligence that is born from machines and develops with machines, going beyond machines. Machines of God? Knowledgeable machines? Or simply deceptive machines?